The Dynamics of Glutathione Species and Ophthalmate Concentrations in Plasma from the VX2 Rabbit Model of Secondary Liver Tumors. (27th January 2011) - Abbas, R.; Kombu, R. S.; Ibarra, R. A.; Goyal, K. K.; Brunengraber, H.; Sanabria, J. R.
Abstract : Purpose . Available tumor markers have low sensitivity/specificity for the diagnosis of liver tumors. The present study was designed to evaluate the oxidoreductive status of the liver as surrogates of tumor subsistence and growth. Methods . Glutathione species (GSH:GSSG), ophthalmate (OA) concentrations, and their turnover were measured in plasma of rabbits (n = 6 ) in their healthy state and in the state of tumor growth after implantation of the VX2 carcinoma in their liver. Tumors were allowed to grow for a period of 14 days when rabbits were sacrificed. Livers were removed and cysteine concentration was measured in liver tissue. Results . Tumor growth was found in 100% of the rabbits. Concentration and labeling of GSH/GSSG were similar in experimental animals before and after tumor implantation and to sham animals. In contrast, OA concentration increased significantly in experimental animals after tumor implantation when compared to same animals prior to tumor implantation and to sham animals (P < . 05 ). The concentration of cysteine, a precursor of GSH, was found to be significantly lower in the liver tissue adjacent to the tumor (P < . 05 ). Conclusion . Disturbances in the oxidoreductive state of livers appear to be a surrogate of early tumor growth.